The importance of social capital in rural development, networking and decision-making in rural areas - Georg Wiesinger (Revue de Géographie Alpine)
Rural decline is frequently explained in economic terms by unfavourable conditions and by missing resources or support. But this link is not entirely clear and does not apply in all regions. Some particularly remote rural regions with a very sparse population, a lack of policy support, poor economic performance and unfavourable climatic conditions prove more viable than some regions with more plentiful economic resources and support. The presentation will discuss the issue whether the concept of social capital could lead to a better understanding of these patterns. The role of social capital will be demonstrated by means of a model connecting it with rural development, multifunctionality, local governance and environmental perception and national policies. The findings of several case studies within the EUROLAN project (Strengthening the Multifunctional Use of Land: Coping with marginalisation), suggest that social capital should be more recognized by policy makers as a key issue in the rural development process, hampering (when weak) or supporting (when strong and well-rooted) the implementation of rural development policies.